The nurse's role in the prevention and diagnosis of malnutrition in patients in Intensive Care - Pierzak, Monika (Journal of Education, Health and Sport, 2019)
Nutritional therapy, also known as clinical treatment is an important component of modern treatment of patients in each of the Polish hospital wards. It includes nutritional assessment, evaluation nutritive requirements and nutritive, an adequate supply of proteins, fats, electrolytes, trace elements and water, taking advantage of the way the gastrointestinal tract, or by intravenous administration [4,5]. In Poland in the Regulation of the Minister of Health of 15 September 2011, the assessment of the nutritional status of the patient, taken on the hospital ward is mandatory excluding patients from emergency departments [6,7,8]. Malnutrition is a disease of multifactorial etiology, in the diagnosis, which plays a very important role cooperation of the whole therapeutic team - nutrition. The nurse, as a member of the team, plays an essential role in the prevention and diagnosis of malnutrition in patients staying in intensive care. Nursing staff, the first to have direct contact with patients, exercising care over him. Direct contact and careful observation, to allow diagnosis of early symptoms of malnutrition [10].Keywords: malnutrition, nurse, prevention